(untitled) (Indonesian Health Justice Review, 2024)
Community health workers (CHWs) play a pivotal role in achieving health justice, particularly in Indonesia’s remote and underserved rural areas. This paper investigates the role of CHWs in delivering essential healthcare services, such as immunizations, maternal and child care, and disease prevention in villages with limited access to formal healthcare facilities. The study employs both qualitative and quantitative methods, including surveys of CHWs, interviews with community members, and field visits to rural villages. Results reveal that while CHWs are crucial in filling gaps in healthcare provision, they face numerous challenges, including inadequate training, limited resources, and insufficient government support. Despite these challenges, CHWs are seen as trusted figures in their communities and are instrumental in improving health outcomes. The paper highlights the need for greater investment in CHW training, infrastructure, and integration into the formal healthcare system to ensure sustainable health justice in remote areas.